Analisis SOAR (Streght, Opportunity, Aspirations, Result) untuk Menentukan Strategi Pemasaran Produk Pelatihan pada Lembaga Pelatihan - Sutantio, Erian (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The large market share for occupational health and safety training institutions makes training institutions want to know the right strategy in marketing so that the market share can be optimally absorbed. The method for determining the marketing strategy used is the SOAR method, then analyzed using EFAS and IFAS to determine the best marketing strategy. After the research was conducted and the analysis, the best strategy was obtained in the SOAR method, namely the strategy in the SO (Strength - Opportunity) quadrant with the activity of opening training with new topics related to occupational health and safety that attract consumers to take part in training, opening cooperation with campuses and providing student prices that can attract the attention of students and campuses so that they can work together, participating in government services related to special training obligations, adding admin and reviewing cooperation with the party providing professional certificates so that they can carry out administration quickly.